1979
DOI: 10.1016/0378-4320(79)90041-1
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial activity and expulsion of fetuses

Abstract: Chronic implantation of extracellular electrodes on successive uterine segments of pregnant miniature sows and marking of their fetuses were performed in order to relate characteristics of uterine electrical activity during delivery with the sequence of expulsion of piglets.The electromyographs during parturition were characterized by synchronic and well propagated phases of activity that could first appear at any of the four electrodes; however, initiation occurred most frequently at the electrodes on the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…The very steep increase in electrical activity, especially long spike bursts, in the uterine horn (Text-figs 3 and 5b) as compared to the body at 72 h pre partum suggests that electrical activity is propagated in the tubocervical direction, thus facilitating the expulsion of the fetus. This is consistent with the findings of Taverne et al (1979a) who reported that phases of propagated activity first appeared at the two ends of the horn in sows during parturition. It has not been possible to estimate the propagation velocity in the present study because several electrodes implanted successively along the uterine axis are required.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The very steep increase in electrical activity, especially long spike bursts, in the uterine horn (Text-figs 3 and 5b) as compared to the body at 72 h pre partum suggests that electrical activity is propagated in the tubocervical direction, thus facilitating the expulsion of the fetus. This is consistent with the findings of Taverne et al (1979a) who reported that phases of propagated activity first appeared at the two ends of the horn in sows during parturition. It has not been possible to estimate the propagation velocity in the present study because several electrodes implanted successively along the uterine axis are required.…”
Section: Discussionsupporting
confidence: 94%
“…The electromyographic activity of the uterus during pregnancy and parturition when the uterus is subjected to the actions of several hormones has been studied by Bosc & Fevre (1974) and Naaktgeboren, Kroon & Schoof (1975). and Sakaguchi & Nakajima (1973) have characterized the electromyographic activity of the uterus during human labour and Bosc, du Mesnil du Buisson & Locatelli (1974), Bosc, Locatelli, Nicolle & du Mesnil du Buisson (1976) and Taverne, Naaktgeboren & van der Weyden (1979a) have studied the uterine changes in pigs at the time of parturition. The pattern of myoelectrical changes in the sheep uterus in the periparturient period was described by Prud'homme & Bosc (1977) and Krishnamurti, Kitts & Tompkins (1979).…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant sows no coordinated uterine motility was observed until one day prae partum (42,43,51). At the onset of parturition contractions appear at regular intervals along the horn with both tubocervical and cervicotubal direction (44,51).…”
Section: Thilander Discussionmentioning
confidence: 99%
“…2006). During the expulsive stage, tubocervically and cervicotubally directed contractions move the piglets forwards and backwards within the uterine horns (Taverne et al. 1979b).…”
Section: Introductionmentioning
confidence: 99%